Editorial [Hot Topic: Tocotrienols: Potential Drug Targets for Cardiovascular, Cancer and Neurological Diseases (Executive Guest Editor: Dipak K. Das)] - K. Das, Dipak (Current Pharmaceutical Design, 2011)
Tocotrienols are a form of vitamin E that have been under the shadow of the popular vitamin E form, α-tocopherol. There are eight forms of vitamin E: four tocopherols (alpha, beta, gamma, delta) and four tocotrienols (alpha, beta, gamma, delta). Tocorienol and tocopherol are similar in that both have the same head called chromanol nucleus, the site of antioxidant activities. Alpha-tocopherol (α-tocopherol) is the most common form in the diet, which is mainly available from many cereal, grains, and oils. Tocotrienols, on the other hand are only minor components present in plants Several sources with relatively high levels of tocotrienols include palm oil, rice bran oil and cereals. While the research on tocotrienols has been traditionally neglected, a number of the most recent studies have shown the potential of tocotrienols for the prevention of many human diseases. The studies also revealed the molecular targets of the tocotrienols and their roles in cancer, bone resorption, diabetes, cardiovascular diseases and neurological problems in both preclinical and clinical levels. Such multi-targeted role of tocotrienols in most degenerative diseases proves them to be ideal candidates for potential nutraceuticals/pharmaceutical agents. Eight reviews are carefully selected from the authorities of tocotrienol research. In one of the reviews, Professor Kailash Prasad from the University of Saskatchewan, Saskatoon, Canada, has discussed beneficial effects of tocotrienols in cardiovascular health. The review emphasis the effects of tocotrienols on the risk factors for atherosclerosis, plaque instability and thrombogenesis and compared these effects with those of tocopherol. The cardioprotective effects of tocotrienols on ischemic injury and its potential beneficial effects on the patients undergoing angioplasty, stent implantation and aorto-coronary bypass surgery are discussed. The authors recognized that although tocotrienols possess potential for cardiovascular health, long-term randomized clinical trials are needed to establish their efficacy in primary and secondary prevention of coronary heart disease. The second review by Professor Belma Turan of the Ankara University and Professor Guy Vassort of the INSERM U, Montpellier, France, deals with the antioxidant action of tocopherols and tocotrienols. This review has recognized the fact that tocotrienols possess antioxidative properties 1600 times more than tocopherols and only tocotrienols in nanomolar concentration can protect neuronal cells from glutamate-induced cell death. The authors have emphasized the use of optimal doses of tocopherol/tocotrienols because at high dosage of over 400 IU/day vitamin E may increase all-cause mortality and should be avoided. At higher doses only vitamin E does not show any health benefits, it is associated with an increase in total mortality, heart failure and hemorrhagic shock. The next review by Professor Vasanthi and Dr. Parameswai from Pondicherry University and Professor Dipak K Das from the University of Connecticut School of Medicine, USA have discussed the importance of tocotrienols in cardiovascular health based on their mechanisms of action. This review discusses how antagonizing the oxidation of low-density lipoproteins inhibition of platelet aggregation is secondary to inhibition of monocyte adhesion and prevention of smooth muscle proliferation. This review recognizes the importance of gamma tocotrienol in heart diseases. A multitude of cardiovascular diseases can be prevented with gamma tocotrienol including hypercholesterolemia, atherosclerosis, ischemic heart disease, hypertension, diabetes and obesity. The supplementation of gamma tocotrienol appears to be essential as dietary sources can provide very little amount of tocotrienol......